Protective effect of antioxidant extracts from Grey oyster mushroom, pleurotus pulmonarius (Agaricomycetes), against human low-density lipoprotein oxidation and aortic endothelial cell damage - Abidin, M.H.Z.; Abdullah, N.; Abidin, N.Z. (Begell House, 2016)
This study evaluated the in vitro antioxidant capacities of extracts from Pleurotus pulmonarius via Folin-Ciocalteu, 1,1-diphenyl-2-picrylhydrazyl free radical scavenging, metal chelating, cupric ion reducing antioxidant capacity, and lipid peroxidation inhibition assays. Extract compositions were determined by phenol–sulfuric acid; Coomassie Plus (Bradford) protein; Spectroquant zinc, copper, and manganese test assays; and liquid chromatography– tandem mass spectrometry (LC/MS/MS) and gas chromatography–mass spectrometry (GC/MS). Methanol-dichloromethane extract, water fraction, hot water, aqueous extract and hexane fraction exhibited the most potent extracts in the antioxidant activities. LC/MS/MS and GC/MS showed that the extracts contained ergothioneine, ergosterol, flavonoid, and phenolic compounds. The selected potent extracts were evaluated for their inhibitory effect against oxidation of human low-density lipoproteins and protective effects against hydrogen peroxide–induced cytotoxic injury in human aortic endothelial cells. The crude aqueous extract was deemed most potent for the prevention of human low-density lipoprotein oxidation and endothelial membrane damage. Ergothioneine might be the compound responsible for the activities, as supported by previous reports. Thus, P. pulmonarius may be a valuable antioxidant ingredient in functional foods or nutraceuticals.